2021
DOI: 10.1212/wnl.0000000000011906
|View full text |Cite
|
Sign up to set email alerts
|

Association of Refractory Pain in the Acute Phase After Subarachnoid Hemorrhage With Continued Outpatient Opioid Use

Abstract: ObjectiveLittle is known about the prevalence of continued opioid use following aneurysmal subarachnoid hemorrhage (aSAH) despite guidelines recommending their use during the acute phase of disease. We sought to determine prevalence of opioid use following aSAH and test the hypothesis that acute pain and higher inpatient opioid dose increased outpatient opioid use.MethodsWe reviewed consecutively admitted aSAH patients from November 2015 through September 2019. We retrospectively collected pain scores and dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 14 publications
(21 reference statements)
0
13
0
Order By: Relevance
“…Although their initial pain scores were low, nearly three of four patients in group 3 continued to use opioids at outpatient follow-up. We have previously reported that persistent, poorly controlled pain during hospitalization was the major contribution to the continuation of opioid use in patients treated for SAH [ 7 ]. Early recognition of high-risk patient trajectories may inform multimodal analgesic strategies aimed at reducing pain, limiting postacute opioid prescriptions, and preventing chronic opioid use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although their initial pain scores were low, nearly three of four patients in group 3 continued to use opioids at outpatient follow-up. We have previously reported that persistent, poorly controlled pain during hospitalization was the major contribution to the continuation of opioid use in patients treated for SAH [ 7 ]. Early recognition of high-risk patient trajectories may inform multimodal analgesic strategies aimed at reducing pain, limiting postacute opioid prescriptions, and preventing chronic opioid use.…”
Section: Discussionmentioning
confidence: 99%
“…We compared outcomes across trajectory groups using the χ 2 or Fisher’s exact test for categorical variable and the Kruskal–Wallis test for ordinal variables. To determine whether trajectory group membership was an independent predictor of outcome, we used logistic regression, adjusting for clinically relevant covariates selected a priori on the basis of previously reported data from this patient cohort: race/ethnicity, a history of depression, a history of opioid use, craniotomy, and insurance type [ 7 ]. We evaluated goodness of fit using a Hosmer–Lemeshow test.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Opioids remain the backbone of pharmacotherapy and may contribute to unacceptably high rates of post-SAH chronic opioid use. 4 Multimodal analgesic strategies are used for other conditions in the intensive care unit in order to limit opioid usage and avoid opioid dependence. 5 More recently, interest has surged in the utilization of nonpharmacological adjuncts to pain management.…”
Section: Introductionmentioning
confidence: 99%
“…Among soldiers returning from active duty who have a TBI diagnosis, nearly 60% are prescribed an opioid during the postdeployment year 21 22. In a study of patients with acute neurological injury suffering from aneurysmal subarachnoid haemorrhage, opioid use was associated with discrete pain trajectories, pain burden and craniotomy 23 24. Opioid sparing during hospitalisations with acute pain is an important component of addressing the current opioid epidemic 25.…”
Section: Introductionmentioning
confidence: 99%